Synthesis of Silica from Rice Husk Ashes with Variation of Solvent (KOH) Concentration - Markha Nisrinah (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2017)
The purpose of this experiment is to utilize natural resources as the candidate of low cost and mass production of silica and to understand the effect of KOH concentration as solvent to the phase structure of silica. The silica was prepared by sol-gel method with rice husk ashes as the raw material from natural resources. The sample was further characterized by X-Ray Diffractometer. The grain size of samples was 490,35 nm, 700,88 nm and 490,44 nm for solvent variation of 5%, 10% and 15% respectively. Those three samples contain silica (SiO2) and magnesium oxide (MgO) obtained from XRD data. ©2017 JNSMR UIN Walisongo. All rights reserved